SOCIALIZATION OF MITIGATION AND ADAPTATION OF LONG-SOURCE PLANS AND ANTIQUITIES OF THE PEOPLE OF AMBON TOWNS WITH SOCIAL CONNECTIVITY - Parera, Evelin; Parera, Lydia R.; Putuhena, Jusmy D; Boreel, Aryanto; Titarsole, Jimmy (LPPM Univ. Ibn Khaldun Bogor, 2024)
Natural disasters such as landslides and droughts pose a serious threat to communities living in the mainland of DAS Waeruhu. Therefore, through a social approach to the community, we call socialization about mitigation and adaptation to the disasters of drought and drought in this region. Some of the problems faced by the communities in the region are: (a) the topography of the district is steep, increasing the risk of droughts, especially during the rainy season; (b) forest deforestation greatly increases the risk for drought due to the loss of soil-resistant vegetation; (c) development without good planning, including building houses on steep slopes, may increase drought risk; (d) changes in irregular rain patterns can cause drought, threatening water supply for agriculture and household needs; (e) rising temperatures and global climate change can worsen drought conditions and reduce available water resources; (f) underprivileged populations may find it difficult to build disaster-resilient infrastructure or take necessary mitigation measures; (g) public awareness of risks and depletion, as well as ways to cope with these risks, can be a serious problem; (h) limited access to education can hinder the public's vital understanding of adaptation and disasters.